Electronic and structural properties of the (001) SrZrO3 surface - Sambrano, J. R.; Longo, V. M.; Longo, Elson [UNESP]; Taft, C. A. (Elsevier B.V., 2007)
The structural and electronic properties of SrZrO3 selected surfaces were investigated by means of density functional theory applied to periodic calculations at B3LYP level. The relaxation effects for two symmetric and asymmetric terminations are analyzed. The electronic and energy band properties are discussed on the basis of band structure as well density of states. There is a more significant rumpling in the SrO as compared to the ZrO2 terminated surfaces. The calculated indirect gap is 4.856, 4.562, 4.637 eV for bulk, ZrO2 and asymmetric terminations, respectively. The gap becomes direct; 4.536 eV; for SrO termination. The contour in the (110) diagonal plane indicates a partial covalent character between Zr and 0 atoms for the SrO terminated surface. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: SrZrO3; perovskite; CRYSTAL; periodic calculations; surfaces; B3LYP